EFL Students’ Perception in Using Duolingo for Developing Speaking Ability - Humairoh, Siti; Martriwati (IKIP Siliwangi, 2025)
English-speaking ability is an essential skill for EFL students to communicate effectively; however, many students face challenges such as limited vocabulary, lack of motivation, and low self-confidence. Therefore, the study